2017
DOI: 10.1177/0040517517729385
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional components from carbon concrete composite C3 – integrated, textile-based sensor solutions for in situ structural monitoring of adaptive building envelopes

Abstract: This contribution will introduce carbon-reinforced concrete components (so-called carbon concrete composites, or C3) with sensor functionalities for innovative building envelopes. For a continuous in situ structural monitoring, these textile-reinforced concrete components are equipped with textile sensor networks consisting of resistive carbon fiber sensors (CFSs), which are integrated into the carbon fiber non-crimp fabrics of the concrete reinforcement by multiaxial warp-knitting. The in situ CFSs, consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, the semi-conductive SiC fibers showed high strain sensitivity with an average GF of 8.25. This GF was very high when compared to electrical resistance strain gauges with GFs of about 2, carbon fibers with GFs of about 2 [15][16][17][18][19][20][21][22][23][24] and CNT coated fibers with GFs of 1.6-2.3 [14] The repeatability on the resistance change measurement for the SiC fibers was evaluated by calculating the coefficient of variation (CV) of the fractional resistance changes at maximum load using equation (4). The results were listed in table 4.…”
Section: Electrical Sensing Properties Of Semi-conductive Sic Fibersmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the semi-conductive SiC fibers showed high strain sensitivity with an average GF of 8.25. This GF was very high when compared to electrical resistance strain gauges with GFs of about 2, carbon fibers with GFs of about 2 [15][16][17][18][19][20][21][22][23][24] and CNT coated fibers with GFs of 1.6-2.3 [14] The repeatability on the resistance change measurement for the SiC fibers was evaluated by calculating the coefficient of variation (CV) of the fractional resistance changes at maximum load using equation (4). The results were listed in table 4.…”
Section: Electrical Sensing Properties Of Semi-conductive Sic Fibersmentioning
confidence: 99%
“…Therefore, utilization of piezoresistivity of the conductive fibers itself can provide an alternative method for measuring the strain of insulating composite materials. As carbon fibers are representative piezoresistive fibers, previous studies have investigated the piezoresistive characteristics of carbon fibers not only for a single carbon fiber [15] but also for carbon fiber bundles such as yarns [16][17][18][19][20][21][22] and rovings [23,24]. It was reported that carbon fibers had the gauge factor (GF) of about 2 and showed excellent linearity in resistance change [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations